Tabloidyzacja a konwergencja mediów – obraz wzajemnych zależności w polskim dyskursie publicznym. Analiza przypadku Tomasza Lisa - Całek, Agnieszka (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The paper is composed of two parts. The first, theoretical part outlines the definitions of convergence and tabloidization. Then, four hypotheses are proposed and developed concerning the mutual relations of these two phenomena. The second part of the paper is devoted to a case analysis of the activity of Tomasz Lis, carried out on the grounds of these four hypotheses. The case study describes how the journalist is affected by tabloidization, while simultaneously using it in his work. The analysis is concluded with the considerations on the activity of Tomasz Lis in the context of media convergence. The paper ends with conclusions on the potential of developing further research in the field of the mutual relations of the phenomena discussed.